IMPLICATIONAL RELEVANCE LOGIC IS 2-EXPTIME-COMPLETE. (22nd January 2016) - SCHMITZ, SYLVAIN
Abstract: We show that provability in the implicational fragment of relevance logic is complete for doubly exponential time, using reductions to and from coverability in branching vector addition systems.